Assessing Cleanliness and Safety at Taman Mini Indonesia Indah Bali Pavilion - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Hakim, Yahdi Nur; La Are, Robert (CV ODIS, 2023)
Taman Mini Indonesia Indah is one of the tourist attractions in Jakarta which has a very large area of 160 hectares and there are 26 pavilions (traditional houses), 13 museums, 10 tourist parks and public and special facilities located far apart. For this reason, visitors really need information services that can help find locations, information and facilities provided at Taman Mini Indonesia Indah.